Anthropocentrism in Christian eco-theology: origin and debate - Maulana, Abdullah Muslich Rizal; Alfionita , Linda; Yahya , Yuangga Kurnia; Untung , Syamsul Hadi (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2024)
This article explores the origins of anthropocentrism in Christian eco-theology, a concept mainly introduced by Lynn White (1907-1987). It also examines the subsequent debates, especially from the perspective of theocentrism, which opposes the Anthropocentric model. Content analysis is used to understand the language and social functions of anthropocentrism and Christian eco-theology in academic literature while also examining the key arguments related to the topic. Meanwhile, discourse analysis is employed to reinforce the findings. The study concludes that Lynn White’s work, The Historical Roots, initiated further contemporary debate on Christian eco-theology. As experts claimed, the error committed by White may have caused tremendous damage to the Christian tradition. However, it also enriched subsequent inquiries into the development of Christian eco-theology. Moreover, the anthropocentric framework in Christian eco-theology was also partly a result of misinterpreting Genesis 1:27, which is closely related to the various interpretations of Imago Dei (image of God). Theocentrism, as such, possibly occupies a central position in present-day apologetics regarding eco-theology in Christianity, providing further opportunities for discussion in defending Christ's relevance to the recent environmental crisis.